Zakat Disbursement Efficiency for Accountability and Prevention of Zakat Misappropriation - Nanang Setiawan; Noorlailie Soewarno (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2024)
This study aims to measure and analyze the efficiency of zakat distribution in Indonesia to achieve accountability and prevent zakat misappropriation. This study uses a desk study to collect data on zakat collection and distribution through the National Zakat Amil Agency (BAZNAS) and twenty-four Zakat Charity Institutions (LAZ) in Indonesia, with two indicators of ratio analysis: disbursement efficiency and cost efficiency. Disbursement efficiency is to see the zakat distribution efficiency level, and cost efficiency is to see the efficiency level of zakat management operational costs. The results show that almost all LAZs have been effective in distributing zakat, except Rumah Yatim Ar Rohman Indonesia (RYARI), with a ratio of 67% (fairly effective). The results of the operational cost efficiency ratio show that only four LAZs fall into the